Material Management in Decentralized Supply Chains - Lee, Hau L.; Billington, Corey (Operations Research, 1993)
A supply chain is a network of facilities that performs the functions of procurement of material, transformation of material to intermediate and finished products, and distribution of finished products to customers. Often, organizational barriers between these facilities exist, and information flows can be restricted such that complete centralized control of material flows in a supply chain may not be feasible or desirable. Consequently, most companies use decentralized control in managing the different facilities at a supply chain. In this paper, we describe what manufacturing managers at Hewlett-Packard Company (HP) see as the needs for model support in managing material flows in their supply chains. These needs motivate our initial development of such a model for supply chains that are not under complete centralized control. We report on our experiences of applying such a model in a new product development project of the DeskJet printer supply chain at HP. Finally, we discuss avenues to develop better models, as well as to fully exploit the power of such models in application.